Effectiveness of remote patient monitoring for wound care: a systematic review - Tanveer, Fateema; Sajwani, Khadeejah; Mohammad Shah Hussain; Yunus, Maliha; Um ul Baneen Zehra (Journal of the Pakistan Medical Association, 2025)
Objective: To evaluate the role of remote patient monitoring with respect to wound care in terms of improving patient outcomes and facilitating the overall care process. Method: The systematic review was conducted from July 2 to October 15, 2023, and comprised literature search on PubMed using key words, including "tele-monitoring", "remote patient monitoring", "telehealth", "telemedicine", "wound care", "home health monitoring", and "self-monitoring". To ensure thorough and robust findings, unpublished studies and solitary abstracts were excluded. To include current research and insights from the modern era, only human studies published from year 2008 to 2023 were included. Results: Of the 51 studies identified, 48(94.11%) were reviewed. After excluding 32(66.66%) irrelevant studies, 16(33.33%) were included for analysis, with 15(93.75%) highlighting favourable results of remote patient monitoring and its efficacy in wound care. Conclusion: Tele-monitoring systems have proven effective with respect to wound care, improving healthcare quality and reducing unnecessary hospital visits through online physician-patient communication. Future research should explore strategies for optimising remote patient monitoring to sustain advancements in wound care practices in Pakistan. Key Words: Tele-monitoring, Remote patient monitoring, Telehealth, Telemedicine, Wound care, Self-monitoring.